Catalytic asymmetric multiple dearomatizations of phenols enabled by a cascade 1, 8-addition and Diels–Alder reaction. Issue 3 (9th December 2019) - Liu, Xihong; Zhang, Jingying; Bai, Lutao; Wang, Linqing; Yang, Dongxu; Wang, Rui
Abstract : The first chiral phosphoric acid catalyzed asymmetric multiple dearomatizations of phenols for the synthesis of bridged polycyclic compounds are reported. Abstract : A direct catalytic asymmetric multiple dearomatization reaction of phenols was disclosed, which provides expedient access to a series of architecturally complex polycyclic compounds bearing four stereogenic centers in high enantiopurity. The key to achieve such a transformation is the combination of a dearomative 1, 8-addition of β-naphthols to para -quinone methides generated in situ from propargylic alcohols and a subsequent intramolecular dearomative Diels–Alder reaction. Noteworthily, this protocol enrichs not only the diversity of dearomatized products but also the toolbox of dearomatization strategies.